2011
DOI: 10.18267/j.polek.801
|View full text |Cite
|
Sign up to set email alerts
|

Potential Product, Output Gap and Uncertainty Rate Associated with Their Determination while Using the Hodrick-Prescott Filter

Abstract: ÚvodV makroekonomických analýzách se často setkáváme s potřebou rozložit časovou řadu na trendovou a cyklickou složku. Tato potřeba vychází z požadavku oddělit od sebe dlouhodobý vývoj a fl uktuace s kratším horizontem. Obě složky jsou potom zpravidla ztotožněny s jistým (přímo neměřitelným) ekonomickým konceptem, přičemž trend je často chápán jako odhad vývoje rovnovážné veličiny a cyklická složka jako dočasná odchylka (mezera) od dlouhodobé rovnovážné trajektorie. V literatuře bylo navrže-no několik metod, j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
(26 reference statements)
0
1
0
1
Order By: Relevance
“…They showed that the difference between results with the constant and variable capital-to-output ratio were not significant. Other studies estimated output gap for the Czech republic with different methods, for example Dybzcak, Flek, Hájková a Hurník (2006), Beneš and N´Diaye (2004), who used multivariate unobserved component model, or Plašil (2011), who analysed univariate HP filter. From newer studies we can mentioned e. g. Kloudová (2013a) who analysed ability of output gap for the Czech republic (methods of estimation were HP filter, SVAR model and multivariate unobserved component model) to indicate inflation.…”
Section: Previous Researchmentioning
confidence: 99%
“…They showed that the difference between results with the constant and variable capital-to-output ratio were not significant. Other studies estimated output gap for the Czech republic with different methods, for example Dybzcak, Flek, Hájková a Hurník (2006), Beneš and N´Diaye (2004), who used multivariate unobserved component model, or Plašil (2011), who analysed univariate HP filter. From newer studies we can mentioned e. g. Kloudová (2013a) who analysed ability of output gap for the Czech republic (methods of estimation were HP filter, SVAR model and multivariate unobserved component model) to indicate inflation.…”
Section: Previous Researchmentioning
confidence: 99%
“…Simulační přístup k určení intervalových odhadů pro mezeru výstupu a potenciální produkt je v praxi nejčastější a v souvislosti s aplikací HP fi ltru jej popisuje např. Plašil (2011).…”
unclassified